Mineral dust aerosol net direct radiative effect during GERBILS field campaign period derived from SEVIRI and GERB. Issue 7 (7th April 2014) - Ansell, C.; Brindley, Helen E.; Pradhan, Yaswant; Saunders, Roger
Abstract : Colocated Spinning Enhanced Visible and Infrared Imager (SEVIRI) retrieved dust optical depths at 0.55 microns, τ 055, and Geostationary Earth Radiation Budget (GERB) fluxes at the top of atmosphere are used to provide, for the first time, an observationally based estimate of the cloud‐free net direct radiative effect (DRE) of mineral dust aerosol from geostationary satellite observations, providing new insights into the influence of time of day on the magnitude and sign of the shortwave, longwave, and overall net effect during sunlit hours. Focusing on the Geostationary Earth Radiation Budget Intercomparison of Longwave and Shortwave radiation (GERBILS) campaign over North Africa during June 2007, the presence of mineral dust aerosol reduces the outgoing longwave radiation at all times of day with the peak reduction clearly following the diurnal cycle of surface temperature. The instantaneous shortwave DRE shows strong dependencies on pristine sky albedo and solar zenith angle such that the same dust loading can induce a positive or negative value dependent on time of day. However, the area mean net DRE over the GERBILS period is dominated by the longwave component at all sampled times of day, with mineral dust inducing a reduction in outgoing net flux of the order of 10W m −2 . Hence, in the mean sense, Saharan dust is found to warm the Earth‐atmosphere system over northern Africa and the Middle East. Key Points: Dust causes a mean net radiative heating seen over the region and period studies Mean net dust effect is dominated by LW component Locally, SW dust radiative effect can dominate and change sign dependent on time of day